(untitled) (Western European Journal of Medicine and Medical Science, 2024)
Cervical cancer (CC) is one of the most common malignancies in women worldwide [1]. The attitude towards cancer as an incurable disease, inevitably leading to painful death, has been formed for decades, mainly during the period when there were no effective drugs and treatment methods. Indeed, not so long ago in modern history, an oncologist’s diagnosis was perceived as an unambiguous death sentence, and every case of recovery was regarded as a miracle Now the situation has changed dramatically: new research methods have emerged, personalised treatment methods have been developed, taking into account the peculiarities of each individual’s organism[9]. A common malignant disease of the organs of the female reproductive system. Modern gynaecological oncology has great opportunities for the treatment of pathology. One of the most effective ways is still considered to be surgery. The choice of intervention protocol depends on the stage of process development, the woman’s desire to have children in the future, and other factors